2018
DOI: 10.1016/j.celrep.2018.03.033
|View full text |Cite
|
Sign up to set email alerts
|

PTCD1 Is Required for 16S rRNA Maturation Complex Stability and Mitochondrial Ribosome Assembly

Abstract: The regulation of mitochondrial RNA life cycles and their roles in ribosome biogenesis and energy metabolism are not fully understood. We used CRISPR/Cas9 to generate heart- and skeletal-muscle-specific knockout mice of the pentatricopeptide repeat domain protein 1, PTCD1, and show that its loss leads to severe cardiomyopathy and premature death. Our detailed transcriptome-wide and functional analyses of these mice enabled us to identify the molecular role of PTCD1 as a 16S rRNA-binding protein essential for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 39 publications
6
54
0
Order By: Relevance
“…Our observation (1) is in line with a recent molecular study of PTCD1 (Perks et al, 2018), which reported that through binding to 16S rRNA and association with FASTKD2 and RPUSD4, PTCD1 facilitates pseudouridinylation and thereby stability of 16S rRNA. Underlining its crucial role in mitoribosome assembly, we find mitoribosome biogenesis disrupted at several stages in the absence of PTCD1.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our observation (1) is in line with a recent molecular study of PTCD1 (Perks et al, 2018), which reported that through binding to 16S rRNA and association with FASTKD2 and RPUSD4, PTCD1 facilitates pseudouridinylation and thereby stability of 16S rRNA. Underlining its crucial role in mitoribosome assembly, we find mitoribosome biogenesis disrupted at several stages in the absence of PTCD1.…”
Section: Discussionsupporting
confidence: 90%
“…HeLa cells are able to entirely switch to glycolysis to compensate for a loss of OXPHOS (Marroquin et al, 2007) and therefore tolerate PTCD1 KO. Their lack of dependency on mitochondrial respiration is a possible reason why the absence of PTCD1 in HeLa cells did not lead to the strong compensatory transcriptional upregulation of 12S and 16S precursor RNA observed here in primary neurons and previously reported in heart and skeletal muscle (Perks et al, 2018).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…CEBPb, ATF4, and CHOP are also key activators of the mitochondrial unfolded protein response (mtUPR) (Higuchi-Sanabria et al, 2018;Moehle et al, 2018); however, we did not observe significant upregulation of mitochondrial proteases in the Mrps12 ep/ep mice, perhaps due to a simultaneous induction of systems that stabilize mitochondrial respiratory complexes, as we observed in these mice at 10 weeks of age. We and others have previously observed increased ATF4 and CHOP in mouse models with impaired mitochondrial translation (Rackham et al, 2016;Seiferling et al, 2016;Perks et al, 2018), and impaired mitochondrial translation can induce mtUPR in worms and mammalian cell culture (Houtkooper et al, 2013). In contrast, loss of the Lon protease in flies activates mtUPR and inhibits mitochondrial translation (Pareek et al, 2018) ◀ Figure 6.…”
Section: Of 19mentioning
confidence: 94%